Setting up a factory in Penang : an integrated approach to total business planning for a construction based SME seeking to diversify into contract manufacturing in Malaysia. - Wong, Yew Cheong. (2009)
This project is based on an actual Singapore-based Small and Medium Enterprise's attempt to diversify its operations into contract manufacturing via the set up of a factory in Penang - Prai.